A Systematic Literatur Review: Exploring the Rich Heritage of Indonesian Cuisine through the Versatile Peanut Ingredient - Nur Agustin Mardiana; Hyldegardis Naisali (G-Tech: Jurnal Teknologi Terapan, 2023)
Peanuts are widely used in Indonesian cuisine as a source of protein and vital fats, and they provide an exceptional nutritional profile that meets the needs of the country's diet. Peanuts, or "kacang tanah," in Indonesia, immerse an important place in Indonesia's traditional dishes. This study mapped the geographical distribution of 85 different varieties of peanuts used in Indonesian cuisine. This review also documents recent developments in the Indonesian peanut dishes, presenting a pioneering culinary profile that enriches national and international culinary databases. This comprehensive review not only explores the method and background of the study but also sheds light on the historical, cultural, and regional aspects of Indonesian culinary heritage thus serve as an invaluable resource for scholars and researchers in fields such as food science, ethnographic culinary science, gastronomy and cultural studies.